Development of non-adherent cell-enclosing domes with enzymatically cross-linked hydrogel shell - Kazama, Ryotaro; Sato, Ryuta; Fujiwara, Hiroyuki; Qu, Yanfei; Nakahata, Masaki; Kojima, Masaru; Fujita, Satoshi; Sakai, Shinji (Biofabrication, 2023)
Non-adherent cells, such as hematopoietic cells and lymphocytes, are important research subjects in medical and biological fields. Therefore, a system that enables the handling of non-adherent cells in solutions in the same manner as that of adhering cells during medium exchange, exposure to chemicals, washing, and staining in imaging applications would be useful. Here, we report a ‘Cell Dome’ platform in which non-adherent cells can be enclosed and grown in the cavities of about 1 mm diameter and 270 μ m height. The domes consist of an alginate-based hydrogel shell of 90 μ m thickness. Cell Domes were formed on glass plates by horseradish peroxidase-mediated cross-linking. Human leukaemia cell line K562 cells enclosed in Cell Domes were stable for 29 days with every 2–3 days of medium change. The enclosed cells grew in the cavities and were stained and differentiated with reagents supplied from the surrounding medium. Additionally, K562 cells that filled the cavities (a 3D microenvironment) were more hypoxic and highly resistant to mitomycin C than those cultured in 2D. These findings demonstrate that the ‘Cell Dome’ may be a promising tool for conveniently culturing and evaluating non-adherent cells.